Analisis Keberlanjutan Integrasi Sapi Sawit Di Kecamatan Bahar Utara, Kabupaten Muaro Jambi: Analysis of the Sustainability of Palm oil and Cattle Integration Farming in North Bahar District, Muaro Jambi Regency - S, Hutwan; Jalius, J; hadi, syafril (Fakultas Peternakan Universitas Jambi, 2019)
Field research was conducted in North Bahar Subdistrict, Muaro Jambi Regency. The research objectives (1) to identify the determinants of the existence of palm oil cattle integration for the future, (2) to formulate a sustainable palm oil-cattle integration policy in the North Bahar District. The results showed that the ecological dimensions was 55.12%. and sensitive factors forage utilization under palm oil plants for cattle feed, economic dimensions 79.60% sensitive factors Company partnership with farmers and social dimensions 52.17% sensitive factors Perception / role of the community in CLS farming. This is indicated to be sufficient to continue the integration system for palm oil- cattle.